1998
DOI: 10.1017/s0048577298970895
|View full text |Cite
|
Sign up to set email alerts
|

Binaural information can converge in abstract memory traces

Abstract: Neural representations for abstract features of auditory stimuli were studied by presenting reading subjects with stimulus blocks composed of pairs of two closely spaced tones. There were frequent ascending standard pairs (i.e., the second tone was higher in frequency than the first tone) and occasional descending deviant pairs. Both types of pairs varied randomly over a wide frequency range. In separate blocks, the tones forming a pair were presented either to the same ear or to opposite ears. The deviant pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…Because MMNm for simple frequency deviation did not differ between the two groups, whereas MMNm to contour and interval changes did, we can conclude that musical training mainly affects the pitch contour and interval relations between tones rather than the encoding of single tones. These results extend a number of recent studies showing that MMN reflects not only the encoding of simple sensory features, but also the encoding of abstract rules and patterns in an auditory context (Trainor et al, 2002;Alain, Achim, & Woods, 1999;Alain, Cortese, et al, 1999;Paavilainen et al, 1998;Alain et al, 1994;Saarinen et al, 1992), by showing differential effects of training on MMNm responses to different types of MMN. The results are also in line with observations of more pronounced MMN responses in musicians to the deviation of musicrelated stimuli, such as harmonic chord progressions (Koelsch, Schröger, & Tervaniemi, 1999), pitch sequences within a tonal structure (Brattico, Näätänen, & Tervaniemi, 2002), and complex temporal patterns of tones (Tervaniemi, Ilvonen, Karma, Alho, & Näätänen, 1997).…”
Section: Discussionsupporting
confidence: 88%
“…Because MMNm for simple frequency deviation did not differ between the two groups, whereas MMNm to contour and interval changes did, we can conclude that musical training mainly affects the pitch contour and interval relations between tones rather than the encoding of single tones. These results extend a number of recent studies showing that MMN reflects not only the encoding of simple sensory features, but also the encoding of abstract rules and patterns in an auditory context (Trainor et al, 2002;Alain, Achim, & Woods, 1999;Alain, Cortese, et al, 1999;Paavilainen et al, 1998;Alain et al, 1994;Saarinen et al, 1992), by showing differential effects of training on MMNm responses to different types of MMN. The results are also in line with observations of more pronounced MMN responses in musicians to the deviation of musicrelated stimuli, such as harmonic chord progressions (Koelsch, Schröger, & Tervaniemi, 1999), pitch sequences within a tonal structure (Brattico, Näätänen, & Tervaniemi, 2002), and complex temporal patterns of tones (Tervaniemi, Ilvonen, Karma, Alho, & Näätänen, 1997).…”
Section: Discussionsupporting
confidence: 88%
“…Second, these features seem not only to be processed independently, but are also integrated in memory trace system as a gestalt-like representation at the same time. MMN was obtained in response to an infrequently presented stimulus produced by conjugating features from two separate standard stimuli (Paavilainen, Jaramillo, & Näätänen, 1998;Sussman, Gomes, Nousak, Ritter, & Vaughan, 1998;Gomes, Bernstein, Ritter, Vaughan, & Miller, 1997). The integrative function in the memory trace is also supported by results showing that the amplitude of MMN to a multiple-feature deviant sometimes approximates the summation of the responses to each single-feature deviation separately (Takegata, Paavilainen, Näätänen, & Winkler, 1999, 2001), but not always this summation works in a linear way (Paavilainen, Valppu, & Näätänen, 2001;Wolff & Schröger, 2001).…”
Section: Introductionmentioning
confidence: 76%
“…The integrative function in the memory trace is also supported by results showing that the amplitude of MMN to a multiple-feature deviant sometimes approximates the summation of the responses to each single-feature deviation separately (Takegata, Paavilainen, Näätänen, & Winkler, 1999, 2001), but not always this summation works in a linear way (Paavilainen, Valppu, & Näätänen, 2001;Wolff & Schröger, 2001). Finally, when acoustic features are combined according to rules or patterns, the invariance of context is also indexed by MMN (Paavilainen, Simola, Jaramillo, Näätänen, & Winkler, 2001;Alain, Achim, & Woods, 1999;Alain, Cortese, & Picton, 1999;Paavilainen, Jaramillo, et al, 1998;Alain, Woods, & Ogawa, 1994). Of interest in the context of the present article is the fact that the representation of auditory features in sensory memory forms part of the neuronal basis of musical processing, and that MMN can be used to examine the presence of memory traces for aspects of complex melodic and harmonic stimuli.…”
Section: Introductionmentioning
confidence: 81%
“…Michie et al (31) have suggested that the relatively greater deficit for duration MMN may derive from the fact that duration processing involves more complex neural computations than simple pitch processing. If this thesis is accurate, then one fertile area for future investigation will be in the use of so-called pattern MMNs (44)(45)(46)(47). In such studies, MMN can be obtained in healthy control subjects where to identify what is constant across stimuli requires generation of an abstract rule on a preattentive basis.…”
Section: Discussionmentioning
confidence: 99%